The moral triangle : Germans, Israelis, Palestinians - Atshan, Sa'ed; Galor, Katharina (Duke University Press, 2020)
How does Germany's legacy of anti-Semitism, Islamophobia, and Holocaust guilt affect the experiences of Israelis and Palestinians living there today? Co-authored by Katharina Galor, who is Israeli-German, and Sa'ed Atshan, who is Palestinian-American, THE MORAL TRIANGLE is an ethnography of immigrant communities in Berlin that shows how migration, trauma, and contemporary state politics are inextricably linked. The authors demonstrate that Germany's steadfast support for the state of Israel challenges Palestinian immigrants, who view this as an abdication of the country's moral responsibility. At the same time, they show that Berlin offers spaces and opportunities for interfaith activism and queer solidarity among Israelis, Germans, and Palestinians, offering a vision of restorative justice that can account for and respond to historical trauma. The book is divided into eleven short chapters, each of which takes up another aspect of the Israeli-Palestinian-German relationship. Atshan and Galor begin by drawing a comparison between the generational trauma resonating from the Holocaust and that from the Nakba, the word Palestinians use to refer to the loss of life and land that happened during the establishment of an Israeli state in 1948. Germans, Israelis, and Palestinians alike assume a narrative link between the Holocaust and the Israel/Palestine conflict - such that Holocaust commemoration programs in Germany, which disproportionately focus on Jewish victims of the Holocaust, are often linked to support for Zionism and the Israeli state. From the perspective of Palestinians in Berlin, this narrative complicates notions of victim and perpetrator, and raises questions about whether the German state has any moral responsibility towards Israel and its treatment of Palestinians. Atshan and Galor then turn to consider Islamophobia and anti-Semitism in Berlin today, highlighting the tension between Chancellor Angela Merkel's policy to welcome refugees from the Middle East and the interpersonal racism experienced by Arab immigrants in Berlin. The next few chapters discuss how this political context has influenced discourse around Israel-Palestine within Germany, including an incident in which Atshan was dramatically disinvited from a widely publicized lecture at the Jewish Museum of Germany. Finally, the authors discuss queer political activism and interfaith initiatives, offering a vision of restorative justice for the German-Israeli-Palestinian triangle grounded in a moral responsibility framework that acknowledges multiple forms of trauma. THE MORAL TRIANGLE will interest students and scholars of religion, anthropology, migration studies, urban studies, and Holocaust and genocide studies, as well as members of the Israeli and Palestinian communities in Germany.